Analisis Pengembangan Wilayah Daerah Malang Utara - Hadi Sumarsono (Jurnal Ekonomi dan Studi Pembangunan, 2015)
Economic development should base on local potential area. It is to be directed to supporting the achievement of improvements in providing support for development planning, resource allocation, spatial and others. Including how to market the products of the sector so that it can be seen and attract investors in its development. The analysis methods used sector is a method of location quotient and Klassen typology, and SWOT. Local economy include the potential economic sectors, and the potential spatial (territorial). 3 covers the economic potential of the sector is quite large, namely agriculture, manufacturing industry and trade, hotels and restaurants; particularly the northern region of Malang shows that the potential level of attractiveness of its economy in general above the district average Malang, unless sub district DAU. FGD and SWOT in the field led to the need for developing a combined approach to ecological factors, and a systems approach activities in order to improve community based economic potential of north Malang.Keywords: Local Economy, FGD, SWOT, approach to ecological factors